2003
DOI: 10.1051/0004-6361:20030512
|View full text |Cite
|
Sign up to set email alerts
|

Stellar evolution with rotation

Abstract: Abstract.We examine the properties of Wolf-Rayet (WR) stars predicted by models of rotating stars taking account of the new mass loss rates for O-type stars and WR stars (Vink et al. 2000(Vink et al. , 2001Nugis & Lamers 2000) and of the wind anisotropies induced by rotation. We find that the rotation velocities v of WR stars are modest, i.e. about 50 km s −1 , not very dependent on the initial v and masses. For the most massive stars, the evolution of v is very strongly influenced by the values of the mass lo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

66
684
4
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 486 publications
(755 citation statements)
references
References 28 publications
66
684
4
1
Order By: Relevance
“…Although the details of the Cassé & Paul calculations are not included in that paper, the 2% that they quote is material ejected only in the WC phase. In both the Higdon & Lingenfelter (2003) and the Meynet & Maeder (2003 models, the ~20% of material includes all material ejected from the birth of the star to the end of the WC phase. Additionally, Cassé & Paul used the solar energetic particle ratio of 0.13 (Mewaldt, et al 1979) instead of the solar wind value of 0.073 (Geiss, 1973) Another important constraint for the origin of cosmic rays, previously obtained from CRIS results, is the requirement that nuclei synthesized and accelerated by SNe are accelerated at least 10 5 yr after synthesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the details of the Cassé & Paul calculations are not included in that paper, the 2% that they quote is material ejected only in the WC phase. In both the Higdon & Lingenfelter (2003) and the Meynet & Maeder (2003 models, the ~20% of material includes all material ejected from the birth of the star to the end of the WC phase. Additionally, Cassé & Paul used the solar energetic particle ratio of 0.13 (Mewaldt, et al 1979) instead of the solar wind value of 0.073 (Geiss, 1973) Another important constraint for the origin of cosmic rays, previously obtained from CRIS results, is the requirement that nuclei synthesized and accelerated by SNe are accelerated at least 10 5 yr after synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…(For details of these models of rotating stars, see Meynet & Maeder, 2003 for the associated nucleosynthesis see Arnould et al 2006.) The end of the WR phase of each star is followed by core collapse.…”
Section: Discussionmentioning
confidence: 99%
“…In massive WCE and WO stars, carbon and oxygen are produced continuously in the non-degenerate He-burning core and are exposed by mass loss stripping (Maeder 1991;Meynet & Maeder 2003). WO stars have number abundance ratios (C+O)/He 0.62 (Kingsburgh et al 1995), initial masses M i > 40 M and WO-lifetimes of 27 000 yr to 62 000 yr, depending on initial mass and rotation on the main sequence (Meynet 2003, private communication).…”
Section: Introductionmentioning
confidence: 99%
“…The classification of the WR star of WR 30a had been taken to be WC4 by Lundström & Stenholm (1984b), and later WO4 by Smith et al (1990a,b) and Crowther et al (1998) companion star has been classified as O4 (Moffat & Seggewiss 1984). Niemela (1995) reported the first radial velocity study for WR 30a, and suggested that WR 30a might be a short period binary.…”
Section: Introductionmentioning
confidence: 99%
“…Maeder et al (2009) write that N/C ratio is sensitive to many parameters such as the age of the star, metallicity, rotation velocity, magnetic field. Evolutionary tracks computed in 2013 are below the tracks designed in 2003 for the same stellar masses (Meynet & Maeder 2003). Cyg OB2 #11 is located above the evolutionary tracks.…”
Section: Locations Of Cyg Ob2 #11 On the Hertzsprung-russell Diagrammentioning
confidence: 87%